Customer service process in the export and import activities of Paxar Bangladesh Limited : a subsidiary of Avery Dennison Corp., USA. - Zakia, Syeda Sulltaniaz (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.